Factors associated with male involvement in the prevention of mother to child transmission of HIV, Midlands Province, Zimbabwe, 2015 - a case control study. (December 2016) - Makoni, Annamercy; Chemhuru, Milton; Chimbetete, Cleopas; Gombe, Notion; Mungati, More; Bangure, Donewell; Tshimanga, Mufuta
Abstract Background Uptake of and adherence to the prevention of mother to child transmission of HIV (PMTCT) interventions are a challenge to most women if there is no male partner involvement. Organizations which include the National AIDS Council and the Zimbabwe AIDS Prevention Project- University of Zimbabwe have been working towards mobilizing men for couple HIV testing and counseling (HTC) in antenatal care (ANC). In 2013, Midlands province had 19 % males who were tested together with their partners in ANC, an increase by 9 % from 2011. However, this improvement was still far below the national target, hence this study was conducted to determine the associated factors. Methods A1:1 unmatched case control study was conducted. A case was a man who did not receive HIV testing and counseling together with his pregnant wife in ANC in Midlands province from January to June 2015. A control was a man who received HIV testing and counseling together with his pregnant wife in ANC in Midlands province from January to June 2015. Simple random sampling was used to select 112 cases and 112 controls. Epi Info statistical software was used to analyze data. Written informed consent was obtained from each study participant. Results Independent factors that predicted male involvement in PMTCT were: having been previously tested as a couple (aOR) 0.22, 95 % CI = 0.12, 0.41) and having time to visit the clinic (aOR) 0.41, 95 % CI = 0.21, 0.80). Being afraid of knowing one's HIV status (aOR 2.22, 95 % CI = 1.04, 4.76) was independently associated with low male involvement in PMTCT. Conclusion Multiple factors were found to be associated with male involvement in PMTCT. Routine PMTCT educational campaigns in places where men gather, community based couple HTC and accommodating the working class during weekends are essential in fostering male involvement in PMTCT thereby reducing HIV transmission to the baby.